Identifikasi Sampah Non organik jenis kaca dan logam di kawasan permukiman RW 6 kelurahan purwosari kecamatan semarang Utara Kota Semarang - Yanuar Adhi Winanta; Maryono Maryono (Jurusan Perencanaan Wilayah dan Kota, 2023)
RW 6 Purwosari Village, North Semarang District is one of the locations in Semarang City that is experiencing solid waste problems. There is still no non-organic waste sorting and processing system in this location. The purpose of this study was to identify non-organic waste types of glass and metal in the residential area of RW 6, Purwosari Village, North Semarang District, Semarang City. In conducting this research, the determination of the survey location was sought using spatial analysis to see the distribution of buildings and residential areas in the research location. Next, a grid analysis will be carried out to determine the survey location. Furthermore, field observations and questionnaires will be distributed to obtain the data needed in the study. Finally, a description of the data obtained during the survey will be carried out. The benefits of this research are data and information about non-organic waste as a basis for making rules in waste processing. The final result that is expected in this research is to obtain information about what and how the level of production of non-organic waste types of glass and metal is obtained in RW 6 Purwosari Village, North Semarang District.